Carbon monoxide as stunning/killing method on farmed Atlantic salmon (Salmo salar): effects on lipid and cholesterol oxidation. (27th August 2015) - Secci, Giulia; Serra, Andrea; Concollato, Anna; Conte, Giuseppe; Mele, Marcello; Olsen, Rolf E; Parisi, Giuliana
Abstract: BACKGROUND: Carbon monoxide (CO) has been recently utilized as a new stunning/killing procedure for Atlantic salmon ( Salmo salar ). Its effects on lipid and cholesterol oxidation of farmed Atlantic salmon fillets were evaluated at two times of refrigerated (2.5 °C) storage, T0 (64 h after death) and T14 (14 days from T0). The use of CO was compared with the commonly utilized percussion (P) method. RESULTS: Fatty acid profile, primary (conjugated dienes) and secondary (TBARS) oxidation products, cholesterol oxidation products (COPs) and carotenoids were unaffected by the killing method. Despite the low oxidative status of lipid (0.66 and 0.60 mg malondialdehyde kg −1 muscle in P and CO fish respectively), cholesterol was found to be highly oxidized (0.17 and 0.13 mg COPs kg −1 ). Storage significantly affected oxidative stability of fish muscle by increasing oxidation products. Interestingly, TBARS content doubled while the increase for COPs was not homogeneous: α ‐ and β ‐epoxycholesterol increased by 25%, whereas triol and 7‐ketocholesterol increased by 48 and 62% respectively. CONCLUSION: The quality of salmon fillets just after slaughtering and after 14 days of refrigerated storage at 2.5 °C did not change, irrespective of the killing method adopted, suggesting that the CO method may be applied without any detrimental effect on the quality of fish fillets. © 2015 Society of Chemical Industry